Magneto-optic properties of highly Dy3+-doped GeO2-B2O3 glasses for NIR optical applications - Linganna Kadathala; Yong-Tak Ryu; Young-Ouk Park; Seongmin Ju; Bok Hyeon Kim (Results in Physics)
Recent progress in the development of optical communication and high power laser systems in the near-infrared (NIR) region (1.5 to 2.0 μm) increased the demand for magneto-optic (MO) devices employing MO materials. These MO materials are required with lower optical absorption coefficients and higher Verdet constants at spectral range of interest. In this study, two series of highly Dy3+-doped GeO2–B2O3 glasses with and without P2O5 were fabricated using a simple melt-quenching technique. The glasses were characterized through various techniques (Raman, UV–VIS-NIR, and DTA) for the evaluation of characteristic properties with respect to the Dy2O3 concentration and glass composition. Faraday rotation measurement was carried out at 1550 nm to quantify the Verdet constant of the glasses. The Verdet constant values were found to increase linearly with increasing Dy3+ concentration for both the glass systems. The increase in Dy3+ concentration and, consequently, the number of unpaired electrons, leads to an increase in the Verdet constant. The GeO2-B2O3 glass doped with 30 mol% of Dy2O3 exhibited the highest Verdet constant of −5.36 rad/(T⋅m) at 1550 nm. The glasses exhibited a good optical transparency (>70 %) in the region covering from 400 to 2400 nm. The thermo-physical, optical, and polarizability properties of both glass systems were also investigated. The results indicate that the highly Dy3+-doped glasses are attractive for magneto-optics at 1550 nm.